2018
DOI: 10.1371/journal.pone.0191896
|View full text |Cite
|
Sign up to set email alerts
|

Modeling for influenza vaccines and adjuvants profile for safety prediction system using gene expression profiling and statistical tools

Abstract: Historically, vaccine safety assessments have been conducted by animal testing (e.g., quality control tests and adjuvant development). However, classical evaluation methods do not provide sufficient information to make treatment decisions. We previously identified biomarker genes as novel safety markers. Here, we developed a practical safety assessment system used to evaluate the intramuscular, intraperitoneal, and nasal inoculation routes to provide robust and comprehensive safety data. Influenza vaccines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…In other words, if the factor of effectiveness becomes excessive, toxic effects may appear. We are currently working on establishing a safety assessment system based on the WPV as a toxicity indicator [60]. The WPV is an effective and excellent vaccine, but the frequency of adverse reactions is high, and currently, it is only rarely used, especially as a prepandemic vaccine.…”
Section: Establishment Of a New Evaluation Methods For Vaccine Or Adjumentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, if the factor of effectiveness becomes excessive, toxic effects may appear. We are currently working on establishing a safety assessment system based on the WPV as a toxicity indicator [60]. The WPV is an effective and excellent vaccine, but the frequency of adverse reactions is high, and currently, it is only rarely used, especially as a prepandemic vaccine.…”
Section: Establishment Of a New Evaluation Methods For Vaccine Or Adjumentioning
confidence: 99%
“…Therefore, we believe that the WPV can be a safety indicator. In other words, we think that there is a high probability that adjuvants and vaccines with innate-immunityinducing activities that exceed the activity (toxicity) of WPVs will cause adverse reactions [60].…”
Section: Establishment Of a New Evaluation Methods For Vaccine Or Adjumentioning
confidence: 99%
“…We have previously reported that it is possible to profile the immunogenicity of inactivated influenza vaccines by analyzing the expression patterns of lung genes within 16 h of priming using genomic analyses (38)(39)(40)(41)(42). In addition, we constructed a novel safety evaluation system for an adjuvanted inactivated influenza vaccine using WPV as a toxicity control via mathematical analyses (43). It has also been reported that these evaluation methods can be applied in mouse (40) and rat (38,39) models, as well as for the evaluation of nasal influenza vaccine (41).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the 18 clustered biomarker genes expressed in the lungs were designated as immunogenicity indicators for influenza vaccines ( Table 1) (38). The biomarker gene expression levels were altered by several adjuvants contained in SV (41)(42)(43). As the present study focuses on influenza vaccine, we used the biomarker gene set similar to those used in our previous studies (39)(40)(41)(42)(43).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation